El salario mínimo en los sectores formal e informal: Evidencia derivada de un choque inflacionario en Colombia - Jorge Pérez Pérez (Banco de México, 2019)
– I estimate the effect of a real minimum wage increase on formal and informal wages, and employment in Colombia. For identification, I take advantage of an unexpected increase in the real minimum wage during 1999, and I compare cities and industries with different incidence of the minimum wage increase. I measure incidence as the percentage of workers whose real minimum wage is between the old and the new real minimum wage before the increase. I find evidence of positive wage responses for wages close to the minimum wage. The results show that wages increase more in the formal than in the informal sector. I do not find that informal wages are reacting to the minimum wage indirectly, through the linkages between formal and informal markets. I show that employers in both sectors use the minimum wage as reference, although they set some wages below it. These results may not be generalizable to other countries or contexts, or to larger minimum wage increases.
Keywords: J31; J38; J46; 330; Minimum wage; wage distribution; informal labor markets